Laminated body for non-aqueous electrolyte secondary battery

By controlling the adhesiveness in a non-hydraulic solution secondary battery laminated body with a polyolefin porous film and porous layer, the peeling risk is mitigated, ensuring structural integrity and safety under external forces.

JP7623112B2Active Publication Date: 2025-01-28エスエスエルエム株式会社
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020123263
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-17
Publication Date
2025-01-28
Estimated Expiration
2040-07-17

AI Technical Summary

Technical Problem

The high adhesiveness between the electrode plate and the separator in non-hydraulic solution secondary batteries can lead to the peeling of the porous layer from the polyolefin porous film when external force is applied, posing a safety risk due to heat resistance and decreased intensity.

Method used

A non-hydraulic solution secondary battery laminated body with a polyolefin porous film and a porous layer on one or both sides, where the adhesiveness between the electrode plate and the porous layer is controlled to ensure the peeling strength is less than the peeling strength between the film, using specific peeling tests to achieve this.

Benefits of technology

The laminated body maintains its structure even under external force, preventing the porous layer from peeling and enhancing safety by moderating the adhesiveness between the electrode plate and the separator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623112000002
    Figure 0007623112000002
  • Figure 0007623112000003
    Figure 0007623112000003
  • Figure 0007623112000004
    Figure 0007623112000004
Patent Text Reader

Abstract

To provide a laminate for a nonaqueous electrolyte solution secondary battery in which a porous layer is not broken easily even in the application of an external force when the laminate exists in the battery.SOLUTION: In a laminate for a nonaqueous electrolyte solution secondary battery according to one embodiment of the present invention, when a peeling test A is carried out, the peeling strength between a first electrode plate (10) and an outermost surface layer of a laminate separator (100a) for a nonaqueous electrolyte solution secondary battery is lower than the peeling strength between a porous layer (30) and a polyolefin porous film (40). Step 1A: a laminate for an aqueous electrolyte solution secondary battery is immersed in a predetermined solvent. Step 2A: the first electrode plate (10) is fixed on a substrate (1000). Step 3A: the laminate separator (100a) for a nonaqueous electrolyte solution secondary battery is peeled under a predetermined condition.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate for a non-aqueous electrolyte secondary battery. The present invention also relates to a member for a non-aqueous electrolyte secondary battery, a non-aqueous electrolyte secondary battery, and a laminate separator for a non-aqueous electrolyte secondary battery. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, particularly lithium ion secondary batteries, have a high energy density and are therefore widely used as batteries for personal computers, mobile phones, portable information terminals, etc., and recently they have been developed as batteries for use in vehicles.

[0003] The power generating element included in the non-aqueous electrolyte secondary battery has a structure in which electrode plates and separators are alternately laminated. From the viewpoint of stability and safety, a technology has been developed to firmly bond the electrode plates and separators together so that this laminated structure can be maintained even when an external force is applied (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-149936 A Summary of the Invention [Problem to be solved by the invention]

[0005] As a separator for a non-aqueous electrolyte secondary battery, a laminate separator in which a porous layer is formed on a polyolefin porous film is widely used. According to the investigations conducted by the present inventors, when a laminate separator for a non-aqueous electrolyte secondary battery is adopted as a separator for a non-aqueous electrolyte secondary battery, the higher the adhesion between the electrode plate and the separator, the more preferable it is. This is because if the adhesion between the electrode plate and the separator is too high, when an external force is applied to the electrode plate-separator laminate, the porous layer may peel off from the polyolefin porous film while remaining attached to the electrode plate. If this peeling occurs inside the battery, a portion with reduced heat resistance and strength will be generated, which may cause a problem in terms of the safety of the battery.

[0006] From the above considerations, the present inventors have found for the first time that there exists a technical demand for a laminate for a non-aqueous electrolyte secondary battery, in which the adhesive strength between the electrode plate and the separator inside the battery is kept at an appropriate strength and the porous layer is not easily broken even when an external force is applied. One aspect of the present invention aims to provide a laminate for a non-aqueous electrolyte secondary battery, in which the porous layer is not easily broken even when an external force is applied while the laminate is inside the battery. [Means for solving the problem]

[0007] The present invention includes the following configurations. <1> A laminate for a non-aqueous electrolyte secondary battery, comprising a first electrode plate and a laminate separator for a non-aqueous electrolyte secondary battery, The laminated separator for a non-aqueous electrolyte secondary battery includes a polyolefin porous film and a porous layer formed on one or both sides of the polyolefin porous film, an outermost layer of the laminated separator for a nonaqueous electrolyte secondary battery in contact with the first electrode plate has adhesiveness to the first electrode plate; A laminate for a non-aqueous electrolyte secondary battery, wherein when a peel test A under the following conditions is performed, the peel strength between the first electrode plate and the outermost layer of the laminate separator for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer and the polyolefin porous film: Step 1A: Immerse the laminate for a non-aqueous electrolyte secondary battery in a solvent having a volume ratio of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate of 30: 35: 35 at 60°C for 24 hours; Step 2A. The first electrode plate is fixed onto a substrate; Step 3A: The laminated separator for a nonaqueous electrolyte secondary battery is peeled off at a peeling speed of 100 mm / min so that the angle between the first electrode plate and the laminated separator for a nonaqueous electrolyte secondary battery is 180°. <2> The peel strength in step 3A is 8 N / m or less. <1> 2. The laminate for a non-aqueous electrolyte secondary battery according to claim 1 . <3> When a peel test B under the following conditions is performed, the peel strength between the first electrode plate and the outermost layer of the laminate separator for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer and the polyolefin porous film. <1> or <2> A laminate for a non-aqueous electrolyte secondary battery according to claim 1, Step 1B: drying the laminate for the non-aqueous electrolyte secondary battery so that the solvent content is 2% or less; Step 2B. Fix the first electrode plate onto a substrate; Step 3B: The laminated separator for a nonaqueous electrolyte secondary battery is peeled off at a peeling speed of 100 mm / min so that the angle between the first electrode plate and the laminated separator for a nonaqueous electrolyte secondary battery is 180°. <4> The first electrode plate is a positive electrode plate, The peel strength in step 3B is 8 N / m or less. <3> 2. The laminate for a non-aqueous electrolyte secondary battery according to claim 1 . <5> The porous layer contains one or more resins selected from the group consisting of (meth)acrylate resins, fluorine-containing resins, polyamide resins, polyimide resins, polyamideimide resins, polyester resins, and water-soluble polymers. <1> ~ <4> 2. The laminate for a non-aqueous electrolyte secondary battery according to claim 1 . <6> The porous layer contains an aramid resin. <1> ~ <5> 2. The laminate for a non-aqueous electrolyte secondary battery according to claim 1 . <7> <1> ~ <6> A non-aqueous electrolyte secondary battery member comprising the laminate for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5 and a second electrode plate, In the non-aqueous electrolyte secondary battery member, the first electrode plate, the non-aqueous electrolyte secondary battery laminate separator, and the second electrode plate are arranged in this order. Components for non-aqueous electrolyte secondary batteries. <8> one of the first electrode plate and the second electrode plate is a positive electrode plate and the other is a negative electrode plate; a peel strength between the positive electrode plate and the laminated separator for the nonaqueous electrolyte secondary battery is smaller than a peel strength between the negative electrode plate and the laminated separator for the nonaqueous electrolyte secondary battery; <7> The non-aqueous electrolyte secondary battery member according to claim 1, <9> <1> ~ <6> 2. The laminate for a non-aqueous electrolyte secondary battery according to claim 1 , <7> or <8> A non-aqueous electrolyte secondary battery comprising the member for a non-aqueous electrolyte secondary battery according to claim 1. <10> A laminate separator for a non-aqueous electrolyte secondary battery, comprising a polyolefin porous film and a porous layer formed on one or both sides of the polyolefin porous film, At least one outermost layer of the laminated separator for a nonaqueous electrolyte secondary battery is located on the porous layer side and has adhesiveness to a test electrode plate, The test electrode plate is a 1 mm thick laminate of an electrode active material consisting of lithium nickel cobalt manganese oxide (NCM523): carbon black: graphite: PVDF = 92: 2.5: 2.5: 3 laminated on an aluminum foil. A laminate separator for a non-aqueous electrolyte secondary battery, wherein when a peel test C under the following conditions is performed, the peel strength between the test electrode plate and the outermost layer of the laminate separator for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer and the polyolefin porous film: Step 1C: Laminating the nonaqueous electrolyte secondary battery laminate separator and the test electrode plate such that the porous layer and the test electrode plate face each other via the outermost layer having adhesiveness to the test electrode plate, and pressing the laminate under conditions of 70° C., 6 MPa, and 10 seconds to prepare a test laminate; Step 2C. Immerse the test laminate in a solvent of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a volume ratio of 30: 35: 35 at 60°C for 24 hours; Step 3C. Fix the test electrode plate onto a substrate; Step 4C: The laminated separator for a non-aqueous electrolyte secondary battery is peeled off at a peeling speed of 100 mm / min so that the angle between the test electrode plate and the laminated separator for a non-aqueous electrolyte secondary battery is 180°. Effect of the Invention

[0008] According to one aspect of the present invention, it is possible to provide a laminate for a non-aqueous electrolyte secondary battery, in which a porous layer is not easily damaged even when an external force is applied to the laminate while the laminate is inside the battery. [Brief description of the drawings]

[0009] [Figure 1] 1 is a schematic diagram illustrating a laminate for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a laminate for a nonaqueous electrolyte secondary battery according to another embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram illustrating a method for a peel test in the present invention. [Figure 4] 1 is a schematic diagram illustrating a nonaqueous electrolyte secondary battery member according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each of the configurations described below, and various modifications are possible within the scope of the claims. The technical scope of the present invention also includes embodiments obtained by appropriately combining the technical means disclosed in different embodiments. In this specification, unless otherwise specified, "A to B" representing a numerical range means "A or more, B or less."

[0011] [1. Laminated body for non-aqueous electrolyte secondary battery] As described above, in a power generating element included in a non-aqueous electrolyte secondary battery, the electrode plate and the separator are usually bonded together to prevent misalignment between the laminated electrode plate and the separator. Conventionally, it has been considered that the stronger the bond, the better.

[0012] However, the inventors have found that when a laminate separator for a non-aqueous electrolyte secondary battery is used as a separator, if the adhesion between the electrode plate and the separator is too high, problems will occur. That is, when an external force is applied to the electrode plate-separator laminate inside the non-aqueous electrolyte secondary battery, the porous layer may peel off from the polyolefin porous film while remaining attached to the electrode plate. Therefore, in a state immersed in the electrolyte, it is preferable that the "peel strength between the electrode plate and the laminate separator for a non-aqueous electrolyte secondary battery" is smaller than the "peel strength between the polyolefin porous film and the porous layer". If such a magnitude relationship of the peel strengths is established, when an external force is applied to the electrode plate-separator laminate inside the non-aqueous electrolyte secondary battery, peeling occurs preferentially between the electrode plate and the porous layer, and peeling of the porous layer from the polyolefin porous film can be prevented.

[0013] In a preferred embodiment, even in a dry state containing almost no electrolyte, the "peel strength between the electrode plate and the laminated separator for a non-aqueous electrolyte secondary battery" is smaller than the "peel strength between the polyolefin porous film and the porous layer." If such a magnitude relationship of the peel strengths is established, when an external force is applied to the electrode plate-separator laminate in a dry state (e.g., during production or transportation of the electrode plate-separator laminate), peeling occurs preferentially between the electrode plate and the porous layer, and peeling of the porous layer from the polyolefin porous film can be prevented.

[0014] In one embodiment of the present invention, a laminate for a non-aqueous electrolyte secondary battery having the above-described peel strength relationship is specified as the result of peel test A and peel test B. Peel test A is a test for determining the magnitude relationship of the peel strength between each layer in the laminate for a non-aqueous electrolyte secondary battery in a state immersed in an electrolyte. Peel test B is a test for determining the magnitude relationship of the peel strength between each layer in the laminate for a non-aqueous electrolyte secondary battery in a dry state.

[0015] Also, one aspect of the present invention provides a laminate separator for nonaqueous electrolyte secondary batteries that is specified by the results of peel test C. Peel test C is a test obtained by modifying peel test A so that it can be applied to laminate separators for nonaqueous electrolyte secondary batteries.

[0016] The adhesiveness between the electrode plate and the laminated separator for non-aqueous electrolyte secondary batteries can be adjusted, for example, by the content of adhesive resin in the porous layer or adhesive layer, the basis weight of the porous layer or adhesive layer, the pressing conditions when preparing the electrode-separator laminate, etc. In general, the higher the content of adhesive resin, the stronger the adhesion tends to be formed. Also, the higher the basis weight of the porous layer or adhesive layer, the stronger the adhesion tends to be formed. Furthermore, the longer the pressing time, the higher the pressing temperature, and the higher the pressing pressure, the stronger the adhesion tends to be formed.

[0017] [Structure of laminate for non-aqueous electrolyte secondary battery] 1 and 2. A laminate 200a (or 200b) for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention includes a first electrode plate 10 and a laminate separator 100a (or 100b) for a nonaqueous electrolyte secondary battery laminated together.

[0018] The first electrode plate 10 may be a positive electrode plate or a negative electrode plate. The first electrode plate 10 has a current collector 12 and an electrode active material layer 15 (positive electrode active material layer or negative electrode active material layer) laminated thereon. The first electrode plate 10 depicted in FIGS. 1 and 2 has the electrode active material layer 15 laminated on one side of the current collector 12 in order to be subjected to a peel test described later. However, the first electrode plate 10 may have a structure in which the electrode active material layer 15 is laminated on both sides of the current collector 12.

[0019] In the laminated separator 100a (or 100b) for a non-aqueous electrolyte secondary battery, a porous layer 30 is formed on one or both sides of a polyolefin porous film 40. In Figs. 1 and 2, an example in which the porous layer 30 is formed on one side of the polyolefin porous film 40 is illustrated.

[0020] In the laminate 200a (or 200b) for a nonaqueous electrolyte secondary battery, the first electrode plate 10 and the laminate separator 100a (or 100b) for a nonaqueous electrolyte secondary battery are laminated so that the electrode active material layer 15 and the porous layer 30 face each other. In this case, the outermost layer of the laminate separator 100a (or 100b) for a nonaqueous electrolyte secondary battery that is in contact with the first electrode plate 10 is a layer that has adhesive properties to the first electrode plate 10. The layer that has adhesive properties to the first electrode plate 10 may be an adhesive layer 20 provided separately from the porous layer 30 (see FIG. 1). Alternatively, the layer that has adhesive properties to the first electrode plate 10 may be the porous layer 30 itself (see FIG. 2).

[0021] [Peel test A] Peel test A is a test for determining the magnitude relationship of peel strength between layers of the laminate 200a (or 200b) for a nonaqueous electrolyte secondary battery in a state immersed in an electrolyte. Peel test A is performed according to the following procedure. (Step 1A) The laminate 200a (or 200b) for a nonaqueous electrolyte secondary battery is immersed in a solvent having a volume ratio of ethylene carbonate:dimethyl carbonate:ethyl methyl carbonate of 30:35:35 at 60° C. for 24 hours. (Step 2A) The first electrode plate 10 is fixed onto the substrate 1000. (Step 3A) The laminated separator 100a (or 100b) for the nonaqueous electrolyte secondary battery is peeled off at a peeling speed of 100 mm / min so that the angle between the first electrode plate 10 and the laminated separator 100a (or 100b) for the nonaqueous electrolyte secondary battery is 180°.

[0022] In step 1A, the nonaqueous electrolyte secondary battery laminate 200a (or 200b) is immersed in a solvent having a predetermined composition. This reproduces the state of the nonaqueous electrolyte secondary battery laminate 200a (or 200b) immersed in an electrolyte. Even if the nonaqueous electrolyte secondary battery laminate 200a (or 200b) has been immersed in a different type of electrolyte (e.g., when removed from a battery product), the conditions of the nonaqueous electrolyte secondary battery laminate 200a (or 200b) to be subjected to the peel test A can be made uniform.

[0023] In step 2A, the first electrode plate 10 is fixed onto the substrate 1000 so that the current collector 12 faces the substrate 1000 (see FIG. 3). As long as the first electrode plate 10 can be fixed to a degree that allows it to withstand a peel test, the material of the substrate 1000 and the method of fixing the first electrode plate 10 are not particularly limited. As an example, the substrate 1000 is a glass epoxy plate. As an example, the first electrode plate 10 is fixed to the substrate 1000 by double-sided tape.

[0024] In step 3A, a peel test device can be used as a device for peeling the laminated separator 100a (or 100b) for a nonaqueous electrolyte secondary battery. A person skilled in the art can select an appropriate peel test device that can achieve the above-mentioned peel test conditions.

[0025] When the non-aqueous electrolyte secondary battery laminate 200a (or 200b) is subjected to the peel test A, the peel strength between the first electrode plate 10 and the outermost layer of the non-aqueous electrolyte secondary battery laminate separator 100a (or 100b) is smaller than the peel strength between the porous layer 30 and the polyolefin porous film 40. Therefore, after step 3A, the porous layer 30 attached to the electrode active material layer 15 is only in a small amount, even if it exists. In one embodiment, the area of ​​the porous layer 30 attached to the electrode active material layer 15 is preferably 5% or less, more preferably 1% or less, and even more preferably 0%, assuming that the area of ​​the porous layer 30 bonded to the electrode active material layer 15 before the peel test A is 100%. In one embodiment, the first electrode plate 10 and the non-aqueous electrolyte secondary battery laminate separator 100a (or 100b) are peeled off at the interface between the electrode active material layer 15 and the porous layer 30.

[0026] The area of ​​the porous layer 30 attached on the electrode active material layer 15 can be measured, for example, by image analysis. Since the electrode active material layer 15 is usually black and the porous layer 30 is nearly white, the area can be measured by distinguishing between the two based on the difference in color tone using appropriate image processing software (such as ImageJ).

[0027] After step 3A, the adhesive layer 20 may be attached onto the electrode active material layer 15 or onto the porous layer 30. The adhesive layer 20 is usually a fairly thin layer, and it is difficult to determine whether it is attached to the electrode active material layer 15 or the porous layer 30. In FIG. 3, the adhesive layer 20 is depicted up to the peeled portion of the laminated separator 100a for a nonaqueous electrolyte secondary battery, but this is merely a convenient depiction.

[0028] After step 3A, the amount of the electrode active material layer 15 adhering to the porous layer 30 is preferably 0%, but a small amount is acceptable. In one embodiment, the area of ​​the electrode active material layer 15 adhering to the porous layer 30 is 5% or less, assuming that the area of ​​the electrode active material layer 15 adhered to the porous layer 30 before peel test A is 100%.

[0029] In step 3A, the peel strength when the laminated separator 100a (or 100b) for non-aqueous electrolyte secondary batteries is peeled off is not particularly limited. This is because in the present invention, it is important that the area of ​​the porous layer 30 attached to the electrode active material layer 15 after step 3A is small (the area of ​​the porous layer 30 peeled off from the polyolefin porous film 40 is small). In one embodiment, the peel strength is preferably 8 N / m or less, more preferably 7 N / m or less, and even more preferably 6 N / m or less. The lower limit of the peel strength is preferably 0.8 N / m or more, and more preferably 1 N / m or more. If the peel strength is within the above range, the adhesion between the first electrode plate 10 and the laminated separator 100a (or 100b) for non-aqueous electrolyte secondary batteries is appropriate in a state immersed in an electrolyte, and the structure of the laminate for non-aqueous electrolyte secondary batteries tends to be maintained.

[0030] In step 3A, the peel strength of the laminated separator 100a (or 100b) for a nonaqueous electrolyte secondary battery can be measured by an appropriate device. The device for measuring the peel strength may be integrated with the device for applying the peel test.

[0031] [Peeling test B] Peel test B is a test for determining the magnitude relationship between the peel strengths of the layers of the laminate 200a (or 200b) for a nonaqueous electrolyte secondary battery in a dry state. Peel test B is performed according to the following procedure. (Step 1B) The laminate for a nonaqueous electrolyte secondary battery 200a (or 200b) is dried so that the solvent content is 2% or less. (Step 2B) The first electrode plate 10 is fixed onto the substrate 1000. (Step 3B) The laminated separator 100a (or 100b) for the nonaqueous electrolyte secondary battery is peeled off at a peeling speed of 100 mm / min so that the angle between the first electrode plate 10 and the laminated separator 100a (or 100b) for the nonaqueous electrolyte secondary battery is 180°.

[0032] In step 1B, the method for removing the solvent from the nonaqueous electrolyte secondary battery laminate 200a (or 200b) is not particularly limited. For example, the solvent can be removed by washing the nonaqueous electrolyte secondary battery laminate 200a (or 200b) taken out of the battery product with a volatile solvent and drying under reduced pressure. In addition, the nonaqueous electrolyte secondary battery laminate 200a (or 200b) before assembly into a battery may be used.

[0033] When the nonaqueous electrolyte secondary battery laminate 200a (or 200b) is subjected to the peel test B, the peel strength between the first electrode plate 10 and the outermost layer of the nonaqueous electrolyte secondary battery laminate separator 100a (or 100b) is smaller than the peel strength between the porous layer 30 and the polyolefin porous film 40. Therefore, even if there is a porous layer 30 attached to the electrode active material layer 15 after step 3B, the amount is only small. In one embodiment, the area of ​​the porous layer 30 attached to the electrode active material layer 15 is preferably 5% or less, more preferably 1% or less, and even more preferably 0%, assuming that the area of ​​the porous layer 30 bonded to the electrode active material layer 15 before the peel test B is 100%. In one embodiment, the first electrode plate 10 and the nonaqueous electrolyte secondary battery laminate separator 100a (or 100b) are peeled off at the interface between the electrode active material layer 15 and the porous layer 30.

[0034] In step 3B, the peel strength when the laminated separator 100a (or 100b) for non-aqueous electrolyte secondary batteries is peeled off is not particularly limited. This is because it is important in the present invention that the area of ​​the porous layer 30 attached to the electrode active material layer 15 after step 3B is small (the area of ​​the porous layer 30 peeled off from the polyolefin porous film 40 is small). In one embodiment, (i) the first electrode plate 10 is a positive electrode plate, and (ii) the above peel strength in step 3B is preferably 8 N / m or less, more preferably 7.5 N / m or less. The lower limit of the above peel strength is preferably 0.8 N / m or more, more preferably 1 N / m or more, even more preferably 1.2 N / m or more, and even more preferably 1.5 N / m or more. If the peel strength is within the above range, the adhesion between the positive electrode plate and the laminated separator 100a (or 100b) for non-aqueous electrolyte secondary batteries in a dry state is appropriate, and the structure of the laminate for non-aqueous electrolyte secondary batteries tends to be maintained.

[0035] Other conditions for the peel test B are the same as those for the peel test A. Therefore, the description will not be repeated.

[0036] 3 illustrates the application of peel test A or peel test B to a laminate 200a for a nonaqueous electrolyte secondary battery, which includes a laminate separator 100a for a nonaqueous electrolyte secondary battery and a first electrode plate 10. However, peel test A or peel test B can also be applied to a laminate 200b for a nonaqueous electrolyte secondary battery, which includes a laminate separator 100b for a nonaqueous electrolyte secondary battery and a first electrode plate 10. Also, peel test A or peel test B can be applied to a laminate (i.e., a nonaqueous electrolyte secondary battery member 500) which includes a second electrode plate on a polyolefin porous film 40.

[0037] [2. Components for non-aqueous electrolyte secondary batteries] Please refer to Fig. 4. A nonaqueous electrolyte secondary battery member 500 according to one embodiment of the present invention includes a nonaqueous electrolyte secondary battery laminate 200a (or 200b) and a second electrode plate 50. The nonaqueous electrolyte secondary battery member 500 includes a first electrode plate 10, a nonaqueous electrolyte secondary battery laminate separator 100a (or 100b), and the second electrode plate 50 arranged in this order.

[0038] When the first electrode plate 10 is a positive plate, the second electrode plate 50 is a negative plate. When the first electrode plate 10 is a negative plate, the second electrode plate 50 is a positive plate.

[0039] When the porous layer 30 is formed on one side of the polyolefin porous film 40, the porous layer 30 is disposed between the first electrode plate 10 and the polyolefin porous film 40. When the porous layer 30 is formed on both sides of the polyolefin porous film, the porous layer 30 is further disposed between the second electrode plate 50 and the polyolefin porous film 40.

[0040] The adhesive layer 20 is an optional configuration, and may be disposed at one or more locations selected from (i) between the first electrode plate 10 and the porous layer 30 provided on the first electrode plate 10 side, (ii) between the polyolefin porous film 40 and the second electrode plate 50, and (iii) between the porous layer 30 provided on the second electrode plate 50 side and the second electrode plate 50. In Fig. 4, the adhesive layer 20 is disposed at (i) and (ii) among the above-mentioned locations.

[0041] In one embodiment, the peel strength between the positive electrode plate and the laminated separator 100a (or 100b) for nonaqueous electrolyte secondary batteries is smaller than the peel strength between the negative electrode plate and the laminated separator 100a (or 100b) for nonaqueous electrolyte secondary batteries. In other words, the negative electrode plate is adhered to the laminated separator 100a (or 100b) for nonaqueous electrolyte secondary batteries more firmly than the positive electrode plate.

[0042] With this configuration, when an external force is applied to the nonaqueous electrolyte secondary battery member 500 inside the battery, the positive electrode plate and the laminated separator 100a (or 100b) for the nonaqueous electrolyte secondary battery are preferentially peeled off, and the adhesion between the negative electrode plate and the laminated separator 100a (or 100b) for the nonaqueous electrolyte secondary battery is maintained. The gap between the negative electrode plate and the laminated separator 100a (or 100b) for the nonaqueous electrolyte secondary battery can cause dendrite formation. Therefore, with the above configuration, even if an external force is applied to the battery, the cause of dendrite formation is less likely to occur, improving the safety of the battery.

[0043] [3. Laminated separator for non-aqueous electrolyte secondary batteries] According to one aspect of the present invention, there is provided a laminate separator 100a (or 100b) for a nonaqueous electrolyte secondary battery in which the peel strength between layers has a predetermined relationship when subjected to peel test C described below. Peel test C includes a step of producing a laminate 200a (or 200b) for a nonaqueous electrolyte secondary battery under predetermined pressing conditions using a predetermined electrode plate. In other words, peel test C is a test obtained by modifying peel test A so that it can be applied to laminate separators for nonaqueous electrolyte secondary batteries by standardizing the test conditions.

[0044] [Peeling test C] Peel test C is a test for determining the magnitude relationship of peel strength of a test laminate including the laminate separator 100a (or 100b) for a nonaqueous electrolyte secondary battery and a test electrode plate when immersed in an electrolyte. Peel test C is performed according to the following procedure. (Step 1C) The laminated separator 100a (or 100b) for non-aqueous electrolyte secondary batteries and the test electrode plate are laminated via the outermost layer having adhesiveness to the test electrode plate, and then pressed at 70°C, 6 MPa, and 10 seconds to prepare a test laminate. (Step 2C) The test laminate is immersed in a solvent having a volume ratio of ethylene carbonate:dimethyl carbonate:ethyl methyl carbonate of 30:35:35 at 60° C. for 24 hours. (Step 3C) A test electrode plate is fixed onto the substrate 1000. (Step 4C) The laminated separator 100a (or 100b) for the non-aqueous electrolyte secondary battery is peeled off at a peeling speed of 100 mm / min so that the angle between the test electrode plate and the laminated separator 100a (or 100b) for the non-aqueous electrolyte secondary battery is 180°.

[0045] At least one of the outermost layers of the laminated separator 100a (or 100b) for a nonaqueous electrolyte secondary battery is located on the porous layer 30 side and has adhesive properties to the test electrode plate. In step 1C, the laminated separator 100a (or 100b) for a nonaqueous electrolyte secondary battery and the test electrode plate are bonded via this outermost layer. The outermost layer having adhesive properties to the test electrode plate may be the adhesive layer 20 provided on the porous layer 30, as in the laminated separator 100a for a nonaqueous electrolyte secondary battery. Alternatively, the outermost layer having adhesive properties to the test electrode plate may be the porous layer 30 itself, as in the laminated separator 100b for a nonaqueous electrolyte secondary battery.

[0046] The test electrode plate used in peel test C was a 1 mm-thick laminate of an electrode active material consisting of lithium nickel cobalt manganese oxide (NCM523):carbon black:graphite:PVDF=92:2.5:2.5:3 laminated on an aluminum foil.

[0047] When the test laminate is subjected to the peel test C, the peel strength between the test electrode plate and the outermost layer of the laminate separator 100a (or 100b) for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer 30 and the polyolefin porous film 40. Therefore, after step 4C, the porous layer 30 attached to the test electrode plate is only in a small amount, even if it exists. In one embodiment, the area of ​​the porous layer 30 attached to the test electrode plate is preferably 5% or less, more preferably 1% or less, and even more preferably 0%, assuming that the area of ​​the porous layer 30 bonded to the test electrode plate before the peel test C is 100%. In one embodiment, the test electrode plate and the laminate separator 100a (or 100b) for a non-aqueous electrolyte secondary battery are peeled off at the interface between the test electrode plate and the porous layer 30.

[0048] In step 4C, the peel strength when the laminated separator 100a (or 100b) for non-aqueous electrolyte secondary batteries is peeled off is not particularly limited. This is because in the present invention, it is important that the area of ​​the porous layer 30 attached to the test electrode plate after step 4C is small (the area of ​​the porous layer 30 peeled off from the polyolefin porous film 40 is small). In one embodiment, the peel strength is preferably 8 N / m or less, more preferably 7 N / m or less, and even more preferably 6 N / m or less. The lower limit of the peel strength is preferably 0.8 N / m or more, and more preferably 1 N / m or more. If the peel strength is within the above range, it can be said that the adhesion between the electrode plate and the laminated separator 100a (or 100b) for non-aqueous electrolyte secondary batteries is appropriate in a state immersed in an electrolyte, and the structure of the laminate for non-aqueous electrolyte secondary batteries tends to be maintained.

[0049] Other conditions for peel test C are the same as those for peel test A. Therefore, the description will not be repeated.

[0050] [4. Materials that make up each component] In this section, we will explain what materials each of the components mentioned in the above sections is made of.

[0051] [Laminated separator for non-aqueous electrolyte secondary batteries] The laminated separator 100a (or 100b) for a non-aqueous electrolyte secondary battery has a porous layer 30 formed on one or both sides of a polyolefin porous film 40. 4 Illustrated in FIG. 1 is a laminate separator 100a (or 100b) for a non-aqueous electrolyte secondary battery in which a porous layer 30 is formed on one side of a polyolefin porous film 40.

[0052] The laminated separator 100a (or 100b) for a nonaqueous electrolyte secondary battery may have an outermost layer that is adhesive to an electrode. As in the laminated separator 100a for a nonaqueous electrolyte secondary battery, an adhesive layer 20 different from the porous layer 30 may be provided as the outermost layer that is adhesive to an electrode. As in the laminated separator 100b for a nonaqueous electrolyte secondary battery, the porous layer 30 itself may be the outermost layer that is adhesive to an electrode. In addition, outermost layers that are adhesive to an electrode may be provided on both sides of the polyolefin porous film 40. In either case, the outermost layer that is adhesive to an electrode is provided on at least one of the surfaces of the laminated separator 100a (or 100b) for a nonaqueous electrolyte secondary battery that contacts an electrode plate (positive electrode plate or negative electrode plate).

[0053] (Polyolefin porous film) The polyolefin porous film has many interconnected pores inside, allowing gas and liquid to pass from one side to the other. The polyolefin porous film can be a substrate for a laminate separator for a non-aqueous electrolyte secondary battery. The polyolefin porous film can melt when the battery generates heat, making the laminate separator for a non-aqueous electrolyte secondary battery non-porous, thereby imparting a shutdown function to the laminate separator for a non-aqueous electrolyte secondary battery.

[0054] Here, the term "polyolefin porous film" refers to a porous film mainly composed of polyolefin resin. Also, "mainly composed of polyolefin resin" means that the proportion of polyolefin resin in the porous film is 50% by volume or more, preferably 90% by volume or more, and more preferably 95% by volume or more of the total material constituting the porous film.

[0055] The polyolefin resin, which is the main component of the polyolefin porous film, is not particularly limited, and examples thereof include homopolymers and copolymers obtained by polymerizing monomers such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, and / or 1-hexene, which are thermoplastic resins. That is, examples of homopolymers include polyethylene, polypropylene, and polybutene, and examples of copolymers include ethylene-propylene copolymers. The polyolefin porous film may be a layer containing these polyolefin resins alone, or a layer containing two or more of these polyolefin resins. Among these, polyethylene is more preferable because it can prevent (shut down) the flow of excessive current at a lower temperature, and in particular, polyethylene with a high molecular weight mainly composed of ethylene is preferable. The polyolefin porous film may contain components other than polyolefins as long as the function is not impaired.

[0056] Examples of polyethylene include low-density polyethylene, high-density polyethylene, linear polyethylene (ethylene-α-olefin copolymer), and ultra-high molecular weight polyethylene. Among these, ultra-high molecular weight polyethylene is more preferred, and has a weight average molecular weight of 5×10 5 ~15×10 6 It is more preferable that the polyolefin resin contains a high molecular weight component having a weight average molecular weight of 1,000,000 or more. In particular, it is more preferable that the polyolefin resin contains a high molecular weight component having a weight average molecular weight of 1,000,000 or more, since the strength of the polyolefin porous film and the laminate separator for non-aqueous electrolyte secondary batteries is improved.

[0057] The thickness of the polyolefin porous film is preferably 3 to 20 μm, more preferably 5 to 17 μm, and even more preferably 5 to 15 μm. If the thickness is 3 μm or more, the functions required of the polyolefin porous film (such as a shutdown function) can be sufficiently obtained. If the thickness is 20 μm or less, a thin laminate separator for a nonaqueous electrolyte secondary battery can be obtained.

[0058] The pore size of the pores in the polyolefin porous film is preferably 0.1 μm or less, and more preferably 0.06 μm or less, which allows sufficient ion permeability to be obtained and further prevents particles constituting the electrode from entering the film.

[0059] The weight per unit area of ​​the polyolefin porous film is usually 4 to 20 g / m2 so as to increase the gravimetric energy density and volumetric energy density of the battery. 2 is preferably 5 to 12 g / m 2 It is more preferable that:

[0060] The polyolefin porous film preferably has an air permeability of 30 to 500 s / 100 mL, more preferably 50 to 300 s / 100 mL, in terms of Gurley value, which allows the laminated separator for non-aqueous electrolyte secondary batteries to have sufficient ion permeability.

[0061] The porosity of the polyolefin porous film is preferably 20 to 80% by volume, and more preferably 30 to 75% by volume, which increases the amount of electrolyte retained and reliably prevents (shuts down) the flow of excessive current at a lower temperature.

[0062] The method for producing the polyolefin porous film can be a known method and is not particularly limited. For example, as described in Japanese Patent No. 5476844, a method in which a filler is added to a thermoplastic resin, a film is formed, and then the filler is removed can be mentioned.

[0063] Specifically, for example, when the polyolefin porous film is formed from a polyolefin resin containing ultra-high molecular weight polyethylene and a low molecular weight polyolefin having a weight average molecular weight of 10,000 or less, from the viewpoint of production costs, it is preferable to produce it by a method including the following steps (1) to (4).

[0064] (1) A process for obtaining a polyolefin-based resin composition by kneading 100 parts by weight of ultra-high molecular weight polyethylene, 5 to 200 parts by weight of a low molecular weight polyolefin having a weight average molecular weight of 10,000 or less, and 100 to 400 parts by weight of an inorganic filler such as calcium carbonate; (2) forming a sheet from the polyolefin resin composition; (3) removing the inorganic filler from the sheet obtained in step (2); (4) A step of stretching the sheet obtained in the step (3). In addition, the methods described in the above-mentioned patent documents may be used.

[0065] Moreover, as the polyolefin porous film, a commercially available product having the above-mentioned characteristics may be used.

[0066] (Porous layer) The porous layer usually contains a filler and a binder resin.

[0067] Types of fillers include organic fillers and inorganic fillers.

[0068] Examples of organic fillers include styrene, vinyl ketone, acrylonitrile, methyl methacrylate, ethyl methacrylate, glycidyl methacrylate, glycidyl acrylate, methyl acrylate, and the like, alone or in copolymers of two or more kinds; fluororesins such as polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, and polyvinylidene fluoride; melamine resin; urea resin; polyolefin; and polymethacrylate. The organic fillers may be used alone or in combination of two or more kinds. Among these organic fillers, polytetrafluoroethylene powder is preferred in terms of chemical stability.

[0069] Examples of inorganic fillers include materials made of inorganic substances such as metal oxides, metal nitrides, metal carbides, metal hydroxides, carbonates, and sulfates. Specific examples include powders of alumina, boehmite, silica, titanium dioxide, aluminum hydroxide, and calcium carbonate. The inorganic fillers may be used alone or in combination of two or more. Among these inorganic fillers, alumina powder is preferred in terms of chemical stability.

[0070] The shape of the filler may be, for example, approximately spherical, plate-like, columnar, needle-like, whisker-like, fibrous, etc., and any of these particles may be used. Approximately spherical particles are preferred because they are more likely to form uniform pores.

[0071] The filler content in the porous layer is preferably 20 to 95% by weight, more preferably 30 to 90% by weight, and further preferably 40 to 90% by weight. The filler content in the porous layer is calculated assuming that the total weight of the porous layer is 100% by weight. By setting the filler content in the above range, a separator with good ion permeability can be obtained.

[0072] The average particle size of the filler contained in the porous layer is preferably 0.01 to 2.0 μm, more preferably 0.05 to 1.0 μm. If the average particle size of the filler is within the above range, in this specification, the "average particle size of the filler" means the volume-based average particle size (D50) of the filler. D50 means the particle size at which the cumulative distribution based on the volume is 50%. D50 can be measured, for example, using a laser diffraction particle size distribution meter (manufactured by Shimadzu Corporation, product name: SALD2200, etc.).

[0073] It is preferable that the binder resin is insoluble in the electrolyte of the battery and is electrochemically stable within the range of use of the battery.

[0074] Examples of binder resins include polyolefins; (meth)acrylate resins; fluorine-containing resins; polyamide resins; polyimide resins; polyamideimide resins; polyester resins; rubbers; resins having a melting point or glass transition temperature of 180°C or higher; water-soluble polymers; polycarbonate, polyacetal, polyether ether ketone, and the like.

[0075] Of the above-mentioned resins, (meth)acrylate resins, fluorine-containing resins, polyamide resins, polyimide resins, polyamideimide resins, polyester resins and water-soluble polymers are preferred.

[0076] As the polyolefin, polyethylene, polypropylene, polybutene, ethylene-propylene copolymer, and the like are preferable.

[0077] Examples of fluorine-containing resins include polyvinylidene fluoride (PVDF), polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trichloroethylene copolymer, vinylidene fluoride-vinyl fluoride copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer, as well as fluorine-containing rubbers having a glass transition temperature of 23° C. or lower among the above-mentioned fluorine-containing resins.

[0078] As the polyamide-based resin, aramid resins such as aromatic polyamides and wholly aromatic polyamides are preferred.

[0079] Specific examples of the aramid resin include poly(paraphenylene terephthalamide), poly(metaphenylene isophthalamide), poly(parabenzamide), poly(metabenzamide), poly(4,4'-benzanilide terephthalamide), poly(paraphenylene-4,4'-biphenylene dicarboxylic acid amide), poly(metaphenylene-4,4'-biphenylene dicarboxylic acid amide), poly(paraphenylene-2,6-naphthalene dicarboxylic acid amide), poly(metaphenylene-2,6-naphthalene dicarboxylic acid amide), poly(2-chloroparaphenylene terephthalamide), paraphenylene terephthalamide / 2,6-dichloroparaphenylene terephthalamide copolymer, metaphenylene terephthalamide / 2,6-dichloroparaphenylene terephthalamide copolymer, etc. Among these, poly(paraphenylene terephthalamide) is more preferable.

[0080] As the polyester-based resin, aromatic polyesters such as polyarylates and liquid crystal polyesters are preferred.

[0081] Examples of rubbers include styrene-butadiene copolymers and hydrogenated products thereof, methacrylate copolymers, acrylonitrile-acrylate copolymers, styrene-acrylate copolymers, ethylene propylene rubber, and polyvinyl acetate.

[0082] Examples of resins having a melting point or glass transition temperature of 180° C. or higher include polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, and polyetheramide.

[0083] Examples of the water-soluble polymer include polyvinyl alcohol, polyethylene glycol, cellulose ether, sodium alginate, polyacrylic acid, polyacrylamide, and polymethacrylic acid.

[0084] The binder resin may be used alone or in combination of two or more kinds.

[0085] (adhesive layer) The adhesive layer bonds the laminated separator for non-aqueous electrolyte secondary batteries to the electrode plate (positive electrode plate or negative electrode plate). The adhesive layer is mainly composed of an adhesive resin. Examples of the adhesive resin include α-olefin copolymers and other adhesive resins.

[0086] In this specification, the term "α-olefin copolymer" refers to a copolymer having structural units derived from an α-olefin and structural units derived from other monomers.

[0087] The α-olefin is preferably an α-olefin having 2 to 8 carbon atoms. Examples of such α-olefins include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, and 1-octene. Among the above-mentioned α-olefins, ethylene is preferable. The structural unit derived from the α-olefin contained in the α-olefin copolymer may be one type or two or more types.

[0088] The other monomer is not particularly limited as long as it is a monomer that can be copolymerized with α-olefin. Examples of such monomers include fatty acid vinyl (vinyl acetate, vinyl propionate, vinyl butyrate, vinyl laurate, vinyl caproate, vinyl stearate, vinyl palmitate, vinyl versatate, etc.); acrylic acid esters having an alkyl group with 1 to 16 carbon atoms (methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, octyl acrylate, lauryl acrylate, etc.); methacrylic acid esters having an alkyl group with 1 to 16 carbon atoms (ethyl methacrylate, methacrylate, etc.); Propyl acrylate, butyl methacrylate, hexyl methacrylate, octyl methacrylate, lauryl methacrylate, etc.); acidic group-containing vinyl monomers (acrylic acid, methacrylic acid, 2-acryloyloxyethyl succinate, 2-methacryloyloxyethyl succinate, carboxyethyl acrylate, carboxyethyl methacrylate, etc.); aromatic vinyl monomers (styrene, benzyl acrylate, benzyl methacrylate, etc.); dienes (1,3-butadiene, isoprene); and acrylonitrile. Among the above-mentioned monomers, fatty acid vinyl, acrylic acid esters, and methacrylic acid esters are preferred, and vinyl acetate and ethyl acrylate are more preferred. The structural units derived from other monomers contained in the α-ethylene copolymer may be of only one type, or may be of two or more types.

[0089] A preferred α-olefin copolymer has (i) structural units derived from an α-olefin and (ii) structural units derived from one or more selected from the group consisting of a vinyl fatty acid, an acrylic acid ester, and a methacrylic acid ester. A more preferred α-olefin copolymer has (i) structural units derived from an α-olefin and (ii) structural units derived from one or more selected from the group consisting of vinyl acetate and ethyl acrylate.

[0090] Examples of adhesive resins other than α-olefin copolymers include fluorine-based polymers (such as polyvinylidene fluoride); ester-based polymers (such as polyethylene terephthalate and polybutylene terephthalate); and cellulose-based polymers (such as carboxymethyl cellulose, carboxyethyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxypropyl cellulose, and carboxyethyl methyl cellulose).

[0091] The thickness of the adhesive layer is preferably 0.005 to 100 μm, more preferably 0.005 to 20 μm, and even more preferably 0.005 to 10 μm. If the thickness of the adhesive layer is within the above range, the internal resistance does not increase significantly when the adhesive layer is used as a member of a nonaqueous electrolyte secondary battery.

[0092] The adhesive layer preferably has a basis weight of 0.0005 to 10 g / m 2 and more preferably 0.0005 to 2.0 g / m 2 and more preferably 0.0005 to 0.25 g / m 2 It is.

[0093] The proportion of the adhesive resin in the adhesive layer is preferably 50% by weight or more, more preferably 70% by weight or more, and even more preferably 90% by weight or more, based on the total weight of the adhesive layer being 100% by weight. In one embodiment, the adhesive layer is substantially composed of only the adhesive resin. If the content of the adhesive resin in the adhesive layer is within the above range, sufficient adhesive strength can be obtained.

[0094] The weight of the adhesive resin in the adhesive layer is preferably 0.001 to 1 g / m 2 and more preferably 0.01 to 1 g / m 2 and more preferably 0.05 to 0.5 g / m 2 The adhesive resin has a weight per unit area of ​​0.001 g / m 2 If the adhesive resin has a weight per unit area of ​​1g / m or more, sufficient adhesive strength can be obtained. 2 If the thickness is equal to or less than this, the internal resistance does not increase significantly when the material is used as a component of a non-aqueous electrolyte secondary battery.

[0095] (Porous layer having adhesive properties) The porous layer itself included in the laminate separator for a nonaqueous electrolyte secondary battery may be configured to have adhesive properties. For example, the porous layer may be made to contain an adhesive resin, thereby forming an adhesive porous layer.

[0096] Examples of adhesive resins that can be contained in the porous layer include the adhesive resins listed in the (adhesive layer) section. The descriptions of other resins and fillers contained in the porous layer are the same as those in the (porous layer) section.

[0097] [Positive electrode] As the positive electrode, for example, a positive electrode sheet having a structure in which an active material layer containing a positive electrode active material and a binder is formed on a current collector can be used. The active material layer may further contain a conductive agent.

[0098] The positive electrode active material may be, for example, a material capable of doping and dedoping lithium ions, such as a lithium composite oxide containing at least one transition metal, such as V, Mn, Fe, Co, or Ni.

[0099] Examples of the conductive agent include carbonaceous materials such as natural graphite, artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fibers, and baked organic polymer compounds.

[0100] Examples of the binder include polyvinylidene fluoride, vinylidene fluoride copolymer, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trichloroethylene copolymer, vinylidene fluoride-vinyl fluoride copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, thermoplastic polyimide, polyethylene, and thermoplastic resin such as polypropylene, acrylic resin, and styrene butadiene rubber. The binder also functions as a thickener.

[0101] Examples of the positive electrode current collector include conductors such as Al, Ni, stainless steel, etc. Among them, Al is more preferable because it is easy to process into a thin film and is inexpensive.

[0102] Examples of methods for producing a sheet-like positive electrode include a method in which a positive electrode active material, a conductive agent, and a binder that constitute a positive electrode mixture are pressure-molded on a positive electrode current collector; a method in which a positive electrode active material, a conductive agent, and a binder are made into a paste using an appropriate organic solvent to obtain a positive electrode mixture, and then the positive electrode mixture is applied to a positive electrode current collector and dried to obtain a sheet-like positive electrode mixture, which is then pressed to be fixed to the positive electrode current collector.

[0103] [Negative electrode] As the negative electrode, for example, a negative electrode sheet having a structure in which an active material layer containing a negative electrode active material and a binder is formed on a current collector can be used. The active material layer may further contain a conductive agent.

[0104] Examples of the negative electrode active material include materials capable of doping and dedoping lithium ions, lithium metal, and lithium alloys. Examples of such materials include carbonaceous materials such as natural graphite, artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fibers, and organic polymer compound sintered bodies; chalcogen compounds such as oxides and sulfides that dope and dedope lithium ions at a lower potential than the positive electrode; metals such as aluminum (Al), lead (Pb), tin (Sn), bismuth (Bi), and silicon (Si) that alloy with alkali metals; and cubic intermetallic compounds (AlSb, Mg ... 2 Si, NiSi 2 ), lithium nitride compounds (Li 3-x M x N (M: transition metal)).

[0105] Examples of the negative electrode current collector include Cu, Ni, stainless steel, etc. Among them, Cu is more preferable, particularly in lithium ion secondary batteries, because it is difficult to form an alloy with lithium and it is easy to process into a thin film.

[0106] Examples of the method for producing a sheet-shaped negative electrode include a method of pressurizing a negative electrode active material to be a negative electrode mixture on a negative electrode current collector, a method of making a negative electrode active material into a paste using an appropriate organic solvent to obtain a negative electrode mixture, applying the negative electrode mixture to a negative electrode current collector, drying the mixture, and pressing the sheet-shaped negative electrode mixture to fix it to the negative electrode current collector, etc. The paste preferably contains the conductive agent and the binder.

[0107] [5. Nonaqueous electrolyte secondary battery] A nonaqueous electrolyte secondary battery according to an embodiment of the present invention includes a nonaqueous electrolyte secondary battery member according to an embodiment of the present invention. The nonaqueous electrolyte secondary battery can be produced, for example, by the following procedure. 1. The non-aqueous electrolyte secondary battery components are placed in a suitable container. 2. Fill the container with non-aqueous electrolyte. 3. The container is sealed while reducing the pressure inside the container.

[0108] [Nonaqueous electrolyte] The non-aqueous electrolyte may be, for example, a non-aqueous electrolyte obtained by dissolving a lithium salt in an organic solvent. 4 , LiPF 6 , LiAsF 6 , LiSbF 6 , LiBF 4 , LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 , LiC(CF 3 SO 2 ) 3 , Li 2 B 10 Cl 10 , lower aliphatic carboxylic acid lithium salts, LiAlCl 4 Among the above lithium salts, LiPF 6 , LiAsF 6 , LiSbF 6 , LiBF 4 , LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 and LiC(CF 3 SO 2 ) 3 At least one fluorine-containing lithium salt selected from the group consisting of:

[0109] Examples of the organic solvent include carbonates such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 4-trifluoromethyl-1,3-dioxolane-2-one, and 1,2-di(methoxycarbonyloxy)ethane; ethers such as 1,2-dimethoxyethane, 1,3-dimethoxypropane, pentafluoropropyl methyl ether, 2,2,3,3-tetrafluoropropyl difluoromethyl ether, tetrahydrofuran, and 2-methyltetrahydrofuran; esters such as methyl formate, methyl acetate, and γ-butyrolactone; nitriles such as acetonitrile and butyronitrile; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; carbamates such as 3-methyl-2-oxazolidone; sulfur-containing compounds such as sulfolane, dimethyl sulfoxide, and 1,3-propane sultone; and fluorine-containing organic solvents obtained by introducing a fluorine group into the above-mentioned organic solvents. Among the organic solvents, carbonates are more preferred, and a mixed solvent of a cyclic carbonate and an acyclic carbonate, or a mixed solvent of a cyclic carbonate and an ether is even more preferred. As a mixed solvent of a cyclic carbonate and an acyclic carbonate, a mixed solvent containing ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate is even more preferred. The mixed solvent has a wide operating temperature range, and is difficult to decompose even when a graphite material such as natural graphite or artificial graphite is used as the negative electrode active material.

[0110] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES

[0111] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0112] [Materials used] In this example, peel test A and peel test B were carried out using the following materials. Positive electrode plate: A positive electrode plate (length: 5 cm x width: 2 cm x thickness: 1 mm) in which the electrode active material consisting of lithium nickel cobalt manganese oxide (NCM523): carbon black: graphite: PVDF = 92: 2.5: 2.5: 3 is laminated on aluminum foil. Negative electrode plate: A negative electrode plate (length: 5 cm x width: 2 cm x thickness: 1 mm) in which electrode active material consisting of graphite:SBR:CMC=98:1:1 is laminated on copper foil. Laminated separator: A laminated separator (length: 10 cm x width: 2.5 cm) in which a porous layer is laminated on one side of a polyethylene porous film. The composition of the porous layer is aramid resin:alumina = 33:67. · Adhesive resin: Ethylene-vinyl acetate copolymer (EVA) or polyvinylidene fluoride (PVDF). Electrolyte: Ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate = 30:35:35 (volume ratio).

[0113] As described above, in this embodiment, the laminate separator is larger in size than the positive and negative electrode plates. When carrying out the peel test, the laminate separator was peeled off by gripping the portion of the laminate separator that was not bonded to the electrode plates.

[0114] [Measurement and test methods] [Peel test A: Peel test while immersed in electrolyte] Peel test A was administered according to the following procedure. 1. The laminate for a non-aqueous electrolyte secondary battery thus prepared was immersed in an electrolyte at 60° C. for 24 hours. 2. The first electrode plate of the laminate for a non-aqueous electrolyte secondary battery was fixed to a substrate (a glass epoxy plate with dimensions of 10 cm length x 3 cm width x 1 mm thickness) using double-sided tape. 3. The laminated separator for the non-aqueous electrolyte secondary battery was peeled off at a peeling speed of 100 mm / min in an atmosphere at 23° C. so that the angle between the first electrode plate and the laminated separator for the non-aqueous electrolyte secondary battery was 180°. RTG-1310 (manufactured by Orientec Co., Ltd.) was used for the peeling. At this time, the peel strength was also measured.

[0115] [Peel test B: Peel test in dry state] Peel test B was administered according to the following procedure. 1. A laminate for a non-aqueous electrolyte secondary battery that was not immersed in an electrolyte was prepared. 2. The first electrode plate of the laminate for a non-aqueous electrolyte secondary battery was fixed to a substrate (a glass epoxy plate with dimensions of 10 cm length x 3 cm width x 1 mm thickness) using double-sided tape. 3. The laminated separator for the non-aqueous electrolyte secondary battery was peeled off at a peeling speed of 100 mm / min in an atmosphere at 23° C. so that the angle between the first electrode plate and the laminated separator for the non-aqueous electrolyte secondary battery was 180°. RTG-1310 (manufactured by Orientec Co., Ltd.) was used for the peeling. At this time, the peel strength was also measured.

[0116] [Check for peeling] After the peel test, the first electrode plate was visually inspected to determine whether or not the porous layer had peeled off.

[0117] [Weight of adhesive layer (EVA)] For laminates for non-aqueous electrolyte secondary batteries using EVA as the adhesive resin, the infrared absorption intensity ratio (IR intensity ratio) was calculated and used as the basis weight of the adhesive layer. -1 ) was measured using the IR intensity characteristic of polyethylene (1470 cm -1 ) was divided by

[0118] [Examples 1 to 5, Comparative Examples 1 to 3] The results of peel test A and peel test B for the laminates for non-aqueous electrolyte secondary batteries according to Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 1. The type of adhesive resin, the basis weight of the adhesive layer, and the pressing conditions when the laminates for non-aqueous electrolyte secondary batteries were produced are as shown in the table.

[0119] [Table 1]

[0120] [Reference example 1] The laminated separator for non-aqueous electrolyte secondary batteries used in the examples and comparative examples was immersed in the electrolyte at 60° C. for 24 hours in the same manner as in peel test A. Next, the peel strength between the polyethylene porous film and the porous layer was measured according to the method specified in JIS-K-6854-2 (Adhesives-Test method for peel adhesion strength-Part 2: 180 degree peeling) and was found to be 8.1 N / m.

[0121] [Reference example 2] The laminated separator for non-aqueous electrolyte secondary batteries used in the examples and comparative examples was prepared in a dry state. Next, the peel strength between the polyethylene porous film and the porous layer was measured according to the method specified in JIS-K-6854-2 (adhesives-peel adhesion strength test method-Part 2: 180 degree peeling), and was found to be 8.0 N / m.

[0122] 〔result〕 As in Examples 1 to 5, by adjusting the type of adhesive resin, the basis weight of the adhesive layer, and the pressing conditions, a laminate for a non-aqueous electrolyte secondary battery having appropriate adhesion between the electrode plate and the separator could be produced. Comparing Examples 1, 3, and 4 with Comparative Examples 1 and 3, it can be seen that the larger the basis weight of the adhesive layer, the higher the adhesion between the electrode plate and the separator tends to be. Comparing Example 5 with Comparative Examples 2 and 3, it can be seen that the higher the pressing pressure, the higher the adhesion between the electrode plate and the separator tends to be.

[0123] In the laminates for nonaqueous electrolyte secondary batteries according to Examples 1 and 2, when the first electrode plate was a positive electrode plate, the porous layer did not peel off even when immersed in an electrolyte solution or when dry, and the laminates had optimal adhesion. In the laminates for nonaqueous electrolyte secondary batteries according to Examples 1 and 2, when the first electrode plate was a negative electrode plate, the porous layer did not peel off even when immersed in an electrolyte solution, which was preferable.

[0124] The results of Examples 1 to 5 and Reference Example 1 suggest that the peel strength in Peel Test A is preferably about 8 N / m or less. The results of Examples 1 and 2 and Reference Example 2 suggest that the peel strength in Peel Test B is preferably about 8 N / m or less. [Industrial Applicability]

[0125] The present invention can be used, for example, in non-aqueous electrolyte secondary batteries. [Explanation of symbols]

[0126] 10:First electrode plate 20: Adhesive layer 30: Porous layer 40:Polyolefin porous film 50:Second electrode plate 100a, b: Laminated separator for non-aqueous electrolyte secondary batteries 200a, b: Laminated body for non-aqueous electrolyte secondary battery 500: Components for non-aqueous electrolyte secondary batteries

Claims

1. A laminate for a non-aqueous electrolyte secondary battery, comprising a first electrode plate and a laminate separator for a non-aqueous electrolyte secondary battery, The laminated separator for a non-aqueous electrolyte secondary battery includes a polyolefin porous film and a porous layer formed on one or both sides of the polyolefin porous film, an outermost layer of the laminated separator for a nonaqueous electrolyte secondary battery in contact with the first electrode plate has adhesiveness to the first electrode plate, A laminate for a non-aqueous electrolyte secondary battery, wherein the peel strength between the first electrode plate and the outermost layer of the laminate separator for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer and the polyolefin porous film when a peel test A under the following conditions is performed: Step 1A: The laminate for a non-aqueous electrolyte secondary battery is immersed in a solvent having a volume ratio of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate of 30: 35: 35 at 60°C for 24 hours; Step 2A. The first electrode plate is fixed onto a substrate; Step 3A: Peel off the laminated separator for a non-aqueous electrolyte secondary battery at a peeling speed of 100 mm / min so that the angle between the first electrode plate and the laminated separator for a non-aqueous electrolyte secondary battery is 180°; Where: The peel strength in step 3A is 0.8 N / m or more; If the area of ​​the porous layer adhered to the electrode active material layer of the first electrode plate before step 1A is 100%, the area of ​​the porous layer adhering to the electrode active material layer after step 3A is 5% or less.

2. A laminate for a non-aqueous electrolyte secondary battery, comprising a first electrode plate and a laminate separator for a non-aqueous electrolyte secondary battery, The laminated separator for a non-aqueous electrolyte secondary battery includes a polyolefin porous film and a porous layer formed on one or both sides of the polyolefin porous film, an outermost layer of the laminated separator for a nonaqueous electrolyte secondary battery in contact with the first electrode plate has adhesiveness to the first electrode plate, A laminate for a non-aqueous electrolyte secondary battery, wherein the peel strength between the first electrode plate and the outermost layer of the laminate separator for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer and the polyolefin porous film when a peel test A under the following conditions is performed: Step 1A: The laminate for a non-aqueous electrolyte secondary battery is immersed in a solvent having a volume ratio of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate of 30: 35: 35 at 60°C for 24 hours; Step 2A. The first electrode plate is fixed onto a substrate; Step 3A: Peel off the laminated separator for a non-aqueous electrolyte secondary battery at a peeling speed of 100 mm / min so that the angle between the first electrode plate and the laminated separator for a non-aqueous electrolyte secondary battery is 180°; Where: The peel strength in step 3A is 0.8 to 8 N / m.

3. 2. The laminate for a non-aqueous electrolyte secondary battery according to claim 1, wherein the peel strength in step 3A is 8 N / m or less.

4. The laminate for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein the peel strength between the first electrode plate and the outermost layer of the laminate separator for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer and the polyolefin porous film when a peel test B under the following conditions is performed: Step 1B: The laminate for a non-aqueous electrolyte secondary battery is dried so that the solvent content is 2% or less; Step 2B. The first electrode plate is fixed onto a substrate; Step 3B: Peel off the laminated separator for a non-aqueous electrolyte secondary battery at a peeling speed of 100 mm / min so that the angle between the first electrode plate and the laminated separator for a non-aqueous electrolyte secondary battery is 180°; Where: The peel strength in step 3B is 0.8 N / m or more; If the area of ​​the porous layer adhered to the electrode active material layer of the first electrode plate before step 1B is 100%, the area of ​​the porous layer adhering to the electrode active material layer after step 3B is 5% or less.

5. The laminate for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein the peel strength between the first electrode plate and the outermost layer of the laminate separator for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer and the polyolefin porous film when a peel test B under the following conditions is performed: Step 1B: The laminate for a non-aqueous electrolyte secondary battery is dried so that the solvent content is 2% or less; Step 2B. The first electrode plate is fixed onto a substrate; Step 3B: Peel off the laminated separator for a non-aqueous electrolyte secondary battery at a peeling speed of 100 mm / min so that the angle between the first electrode plate and the laminated separator for a non-aqueous electrolyte secondary battery is 180°; Where: The peel strength in step 3B is 0.8 to 8 N / m.

6. The first electrode plate is a positive electrode plate, The peel strength in step 3B is 8 N / m or less. The laminate for a non-aqueous electrolyte secondary battery according to claim 4 or 5.

7. The laminate for a nonaqueous electrolyte secondary battery according to any one of claims 1 to 6, wherein the porous layer contains one or more resins selected from the group consisting of (meth)acrylate-based resins, fluorine-containing resins, polyamide-based resins, polyimide-based resins, polyamideimide-based resins, polyester-based resins, and water-soluble polymers.

8. 8. The laminate for a non-aqueous electrolyte secondary battery according to claim 1, wherein the porous layer contains an aramid resin.

9. A non-aqueous electrolyte secondary battery member comprising the laminate for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 8 and a second electrode plate, In the non-aqueous electrolyte secondary battery member, the first electrode plate, the non-aqueous electrolyte secondary battery laminate separator, and the second electrode plate are arranged in this order. Components for non-aqueous electrolyte secondary batteries.

10. one of the first electrode plate and the second electrode plate is a positive electrode plate and the other is a negative electrode plate; a peel strength between the positive electrode plate and the laminated separator for the nonaqueous electrolyte secondary battery is smaller than a peel strength between the negative electrode plate and the laminated separator for the nonaqueous electrolyte secondary battery; The member for a non-aqueous electrolyte secondary battery according to claim 9 .

11. A nonaqueous electrolyte secondary battery comprising the laminate for a nonaqueous electrolyte secondary battery according to any one of claims 1 to 8, or the member for a nonaqueous electrolyte secondary battery according to claim 9 or 10.

12. A laminate separator for a non-aqueous electrolyte secondary battery, comprising a polyolefin porous film and a porous layer formed on one or both sides of the polyolefin porous film, At least one outermost layer of the laminated separator for a nonaqueous electrolyte secondary battery is located on the porous layer side and has adhesiveness to a test electrode plate, The test electrode plate is a 1 mm-thick laminate obtained by laminating an electrode active material consisting of lithium nickel cobalt manganese oxide (NCM523): carbon black: graphite: PVDF = 92: 2.5: 2.5: 3 on an aluminum foil. A laminate separator for a non-aqueous electrolyte secondary battery, wherein the peel strength between the test electrode plate and the outermost layer of the laminate separator for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer and the polyolefin porous film when a peel test C under the following conditions is performed: Step 1C: The nonaqueous electrolyte secondary battery laminate separator and the test electrode plate are laminated together such that the porous layer and the test electrode plate face each other via the outermost layer having adhesiveness to the test electrode plate, and pressed under conditions of 70° C., 6 MPa, and 10 seconds to produce a test laminate; Step 2C. The test laminate is immersed in a solvent having a volume ratio of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate of 30: 35: 35 at 60°C for 24 hours; Step 3C. The test electrode plate is fixed onto a substrate; Step 4C. Peel off the laminated separator for a non-aqueous electrolyte secondary battery at a peeling speed of 100 mm / min so that the angle between the test electrode plate and the laminated separator for a non-aqueous electrolyte secondary battery is 180°; Where: The peel strength in step 4C is 0.8 N / m or more; If the area of ​​the porous layer adhered to the electrode active material layer of the test electrode plate before step 1C is 100%, the area of ​​the porous layer adhering to the electrode active material layer after step 4C is 5% or less.

13. A laminate separator for a non-aqueous electrolyte secondary battery, comprising a polyolefin porous film and a porous layer formed on one or both sides of the polyolefin porous film, At least one outermost layer of the laminated separator for a nonaqueous electrolyte secondary battery is located on the porous layer side and has adhesiveness to a test electrode plate, The test electrode plate is a 1 mm-thick laminate obtained by laminating an electrode active material consisting of lithium nickel cobalt manganese oxide (NCM523): carbon black: graphite: PVDF = 92: 2.5: 2.5: 3 on an aluminum foil. A laminate separator for a non-aqueous electrolyte secondary battery, wherein the peel strength between the test electrode plate and the outermost layer of the laminate separator for a non-aqueous electrolyte secondary battery is smaller than the peel strength between the porous layer and the polyolefin porous film when a peel test C under the following conditions is performed: Step 1C: The nonaqueous electrolyte secondary battery laminate separator and the test electrode plate are laminated together such that the porous layer and the test electrode plate face each other via the outermost layer having adhesiveness to the test electrode plate, and pressed under conditions of 70° C., 6 MPa, and 10 seconds to produce a test laminate; Step 2C. The test laminate is immersed in a solvent having a volume ratio of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate of 30: 35: 35 at 60°C for 24 hours; Step 3C. The test electrode plate is fixed onto a substrate; Step 4C. Peel off the laminated separator for a non-aqueous electrolyte secondary battery at a peeling speed of 100 mm / min so that the angle between the test electrode plate and the laminated separator for a non-aqueous electrolyte secondary battery is 180°; Where: The peel strength in step 4C is 0.8 to 8 N / m.

Citation Information

Patent Citations

  • Secondary battery separator, method for manufacturing secondary battery separator, and secondary battery

    JP2014149936A

  • Adhesive agent for lithium ion secondary batteries, separator with adhesion layer, electrode with adhesion layer, and lithium ion secondary battery

    JP2015041603A

  • Separator for electrochemical element, method for manufacturing same, and electrochemical element including same

    JP2020537290A

  • Separator and electrochemical device containing the same

    KR1020180018408A

  • Nonaqueous secondary battery separator and nonaqueous secondary battery

    WO2012137374A1